2015
DOI: 10.1080/00837792.2015.1005908
|View full text |Cite
|
Sign up to set email alerts
|

Foliar phytoliths as an aid to the identification of Paniceae (Panicoideae: Poaceae) grasses in South India

Abstract: Foliar phytolith studies were carried out in 13 genera including 29 commonly occurring species of the tribe Paniceae of the subfamily Panicoideae (Family: Poaceae) to determine the variations that exist in the phytolith characters, thereby assessing their value in identifying the species. Phytoliths were studied intact in epidermal peeling and also after isolation in acid medium. The members of the tribe were observed to produce a wide variety of lobate phytoliths including bilobate simple type, bilobate nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…Foliar epidermal anatomy study of A. donax, P. monspeliensis, Phragmites karka, C. dactylon, and D. annulatum show similar stomata type paracytic types with the recent study of (Khan et al, 2017) working on family Poaceae. E. colona have tetragonal epidermal cells in our finding while (Ferreira et al, 2002;Jattisha, Sabu, 2015) studied showed that the species had wavy cells. The shape of epidermal cells in P. major in our study showed polygonal shape, while in the study of (Ahmad (Lan et al, 2008) leaf epidermal anatomy of R. scleratus was irregular to polygonal while in our study the shape of the cells is wavy.…”
Section: Trichomes Morphologysupporting
confidence: 50%
“…Foliar epidermal anatomy study of A. donax, P. monspeliensis, Phragmites karka, C. dactylon, and D. annulatum show similar stomata type paracytic types with the recent study of (Khan et al, 2017) working on family Poaceae. E. colona have tetragonal epidermal cells in our finding while (Ferreira et al, 2002;Jattisha, Sabu, 2015) studied showed that the species had wavy cells. The shape of epidermal cells in P. major in our study showed polygonal shape, while in the study of (Ahmad (Lan et al, 2008) leaf epidermal anatomy of R. scleratus was irregular to polygonal while in our study the shape of the cells is wavy.…”
Section: Trichomes Morphologysupporting
confidence: 50%
“…Shaheen et al () also carried out studies on the epidermal leaf morphology of 5 species of genus Setaria ( S.glauca, S.italica, S. tomentosa, S. verticillata, and S. viridis ) with Light and SEM microscope and found significant variation within the species useful in the systematic delimitation of problematic taxa like Setaria . Jattisha and Sabu () also reported that taxonomic importance of foliar phytoliths in the identification of grasses in South India. From all previous work it is well established that foliar anatomy and epidermal features are very important in grass systematics and has significant utilization for characterization of broad groups, within subfamilies, tribes and delimitation of species.…”
Section: Introductionmentioning
confidence: 97%
“…The genus is characterized by the production of large sized bilobate forms with long or very long shanks according to the size based classification provided in our previous paper [7]. Gallego & Distel (2004) [8] reported similar observations in A. subulata. Aristida being a species growing in sub arid regions, presence of long shanks and large sized phytoliths can be attributed to grasses growing in semi arid regions.…”
Section: Discussionmentioning
confidence: 94%